The dynamism of strategic learning: Complexity theory in strategic L2 development - Amerstorfer, Carmen M. (Studies in Second Language Learning and Teaching, 2020)
Learners of foreign languages (L2s) apply strategies to support learning processes and L2 development. They select strategies according to their individual needs and preferences and adjust their strategic actions to suit situational circumstances and contextual conditions. A holistic investigation of strategic L2 learning processes requires the integration of numerous interconnected, flexibly-interacting influences, which are at constant interplay with each other and whose development is difficult to predict. Validated as effective in other fields of applied linguistics, complex dynamic systems theory (CDST) can also provide an appropriate frame for researching strategic L2 learning. Based on state-of-the-art methodological guidance for complexity research, this article presents the re-analysis of empirical data from a previous study through a complexity lens. It further examines the suitability of CDST in strategy research, explores its practical value, and demonstrates that a complexity perspective can generate new, profound information about strategic learning.